2017
DOI: 10.1111/exd.13410
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Beclin‐1‐dependent autophagy promotes ursolic acid‐induced apoptosis in hypertrophic scar fibroblasts

Abstract: A hypertrophic scar (HS) is caused by abnormal proliferation of dermal fibroblasts.Thus, promoting hypertrophic scar fibroblast (HSFB) apoptosis is an effective strategy for HS therapy. Ursolic acid (UA) has been widely used as an inducer of apoptosis in diverse cancers. However, whether UA plays an inhibitory role in HS formation is still unknown. In our study, UA was used to treat HSFBs and the cell viability, apoptosis, and collagen synthesis were determined by a Cell Counting Kit 8 assay, flow cytometry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
(45 reference statements)
3
16
0
Order By: Relevance
“…LC3, Beclin 1 and ATG5 have been confirmed to play regulatory roles in cell autophagy. 37,38 Consistent with these data, the present study confirmed that DHA induced autophagy in HTFs via the mediation of these three proteins. In addition, Chen et al 5 indicated that DHA inhibited esophageal cancer cell migration via inducing autophagy.…”
supporting
confidence: 90%
“…LC3, Beclin 1 and ATG5 have been confirmed to play regulatory roles in cell autophagy. 37,38 Consistent with these data, the present study confirmed that DHA induced autophagy in HTFs via the mediation of these three proteins. In addition, Chen et al 5 indicated that DHA inhibited esophageal cancer cell migration via inducing autophagy.…”
supporting
confidence: 90%
“…Hypertrophic scars and keloids are the two major types of fibrotic skin pathologies induced in response to wounding. Their mechanisms, similarities and differences have been the subject of intense research, as exemplified by recent papers in Experimental Dermatology 59–64 . This topic is also highlighted in several reviews in this issue.…”
Section: Scarring Disorders Of the Skinmentioning
confidence: 92%
“…Several mechanisms have been proposed that may explain the beneficial pharmacological effects by Seo et al: UA is involved in the regulation of the atrophic and metabolic signaling in skeletal muscle, inflammation and antioxidant levels in the brain, NF-κB, and apoptotic signaling in cancer cells, metabolic signaling and oxidant levels in the liver, insulin signaling in tissues, and the expression of markers of heart damage in the heart [115]. Numerous in vitro and in vivo studies have confirmed the anti-cancer properties of this compound through the following mechanisms: Promoting autophagy [128,129], modulating apoptosis [130], inhibiting oncogenesis [131], and proliferation of cancer cells [132], and preventing the cell cycle arrest [19]. There are attempts to apply the UA in inhibiting EMT, especially in GC.…”
Section: Ursolic Acidmentioning
confidence: 99%